A Dynamic Role of the Medial Temporal Lobe during Retrieval of Declarative Memory in Man - Petersson, Karl Magnus; Elfgren, Christina; Ingvar, Martin (NeuroImage (Orlando, Fla.), 1997)
Understanding the role of the medial temporal lobe (MTL) in learning and memory is an important problem in cognitive neuroscience. Memory and learning processes that depend on the function of the MTL and related diencephalic structures (e.g., the anterior and mediodorsal thalamic nuclei) are defined as declarative. We have studied the MTL activity as indicated by regional cerebral blood flow with positron emission tomography and statistical parametric mapping during recall of abstract designs in a less practiced memory state as well as in a well-practiced (well-encoded) memory state. The results showed an increased activity of the MTL bilaterally (including parahippocampal gyrus extending into hippocampus proper, as well as anterior lingual and anterior fusiform gyri) during retrieval in the less practiced memory state compared to the well-practiced memory state, indicating a dynamic role of the MTL in retrieval during the learning processes. The results also showed that the activation of the MTL decreases as the subjects learn to draw abstract designs from memory, indicating a changing role of the MTL during recall in the earlier stages of acquisition compared to the well-encoded declarative memory state.